2010
DOI: 10.5142/jgr.2010.34.1.059
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Chemical Changes in Explosively Puffed Ginsengvand the Optimization of Puffing Conditions

Abstract: :Response surface methodology was used to predict the optimum conditions of explosive puffing process for ginseng. A central composite design was used to monitor the effect of moisture content and puffing pressure on dependent variables such as functional compounds (extract yield, crude saponin, acidic polysaccharide, and total phenolic content) and sensory properties. Correlation coefficients (R 2 ) of models for crude saponin, acidic polysaccharide, and total phenolic content were 0.9176 (p<0.05), 0.9494 (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…It was reported that several polar ginseng saponins were transformed into lower molecular weight non-polar saponins during ginseng roasting [24]. As reported by Yoon et al [32], an increase in crude saponin content after puffing was associated with a reduction in the molecular weight of saponin due to heat treatment and with the facilitation of saponin solubilization caused by the disruption of cell walls.…”
Section: Effect Of Puffing Processmentioning
confidence: 85%
“…It was reported that several polar ginseng saponins were transformed into lower molecular weight non-polar saponins during ginseng roasting [24]. As reported by Yoon et al [32], an increase in crude saponin content after puffing was associated with a reduction in the molecular weight of saponin due to heat treatment and with the facilitation of saponin solubilization caused by the disruption of cell walls.…”
Section: Effect Of Puffing Processmentioning
confidence: 85%
“…Black ginseng is prepared by repeated cycles of atmospheric steaming and sun-drying [13]. Puffed ginseng is prepared by applying an optimized puffing pressure and residual moisture content in ginseng [14]. Fermentation with intestinal microbial flora leads to structural modification of the ginsenosides.…”
Section: Types Of Ginseng Preparationsmentioning
confidence: 99%
“…Park et al (25) reported that some polar ginseng saponins were transformed into smaller non-polar ginseng saponins after roasting, resulting in increased crude saponin contents. Yoon et al (20) suggested that the higher crude saponin content of puffed ginseng was attributable to the enhanced solubility of heat-destroyed cell walls, as well as to a decrease in the molecular mass of saponin due to heat and pressure processes.…”
Section: Contentmentioning
confidence: 99%
“…Recently, it was reported that puffed ginseng showed a higher extraction yield and increased levels of crude saponins, total phenolic compounds, and acidic polysaccharides, compared with non-puffed raw and red ginsengs (18)(19)(20). In addition, Kim et al (19) reported that levels of the major ginsenosides Rb1, Rb2, Rc, Rd, Re, and Rg1 in puffed ginseng were reduced as the puffing pressure was increased; consequently, production levels of ginsenoside Rg3 after puffing indicated changes in the chemical structures of one or more major ginsenosides.…”
Section: Introductionmentioning
confidence: 99%